Flower preferences and pollen transport networks for cavity‐nesting solitary bees: Implications for the design of agri‐environment schemes. Issue 15 (7th July 2018) - Gresty, Catherine E. A.; Clare, Elizabeth; Devey, Dion S.; Cowan, Robyn S.; Csiba, Laszlo; Malakasi, Panagiota; Lewis, Owen T.; Willis, Katherine J.
Abstract: Floral foraging resources are valuable for pollinator conservation on farmland, and their provision is encouraged by agri‐environment schemes in many countries. Across Europe, wildflower seed mixtures are widely sown on farmland to encourage pollinators, but the extent to which key pollinator groups such as solitary bees exploit and benefit from these resources is unclear. We used high‐throughput sequencing of 164 pollen samples extracted from the brood cells of six common cavity‐nesting solitary bee species ( Osmia bicornis, Osmia caerulescens, Megachile versicolor, Megachile ligniseca, Megachile centuncularis and Hylaeus confusus ) which are widely distributed across the UK and Europe. We documented their pollen use across 19 farms in southern England, UK, revealing their forage plants and examining the structure of their pollen transport networks. Of the 32 plant species included currently in sown wildflower mixes, 15 were recorded as present within close foraging range of the bees on the study farms, but only Ranunculus acris L. was identified within the pollen samples. Rosa canina L. was the most commonly found of the 23 plant species identified in the pollen samples, suggesting that, in addition to providing a nesting resource for Megachile leafcutter bees, it may be an important forage plant for these species. Higher levels of connectance and nestedness were characteristic of pollen transport networks on farms with abundant floral resources, which may increase resilience to species loss. Our data suggest that plant species promoted currently by agri‐environment schemes are not optimal for solitary bee foraging. If a diverse community of pollinators is to be supported on UK and European farmland, additional species such as R. canina should be encouraged to meet the foraging requirements of solitary bees. Abstract : The provision of floral foraging resources for wild insect pollinators on farmland, through the sowing of wildflower seed mixtures, is encouraged by agri‐environment schemes in many countries; however, the extent to which key pollinator groups such as solitary bees exploit and benefit from these resources is unclear. We used high‐throughput sequencing of 164 pollen samples extracted from the brood cells of six common solitary bee species to document pollen use by cavity‐nesting solitary bees across 19 farms in southern England, UK. Our data suggest that the current species mix in wildflower seed mixtures is not optimal for solitary bees, and that agri‐environment management should seek to encourage hedgerow species such as Rosa canina to enhance the stability of cavity‐nesting solitary bee communities and their delivery of pollination services.